2019
DOI: 10.3390/en12173334
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Viscosity, Surface Tension and Wetting Behavior Studies of Paraffin–in–Water Nano–Emulsions

Abstract: This work analyzes the dynamic viscosity, surface tension and wetting behavior of phase change material nano–emulsions (PCMEs) formulated at dispersed phase concentrations of 2, 4 and 10 wt.%. Paraffin–in–water samples were produced using a solvent–assisted route, starting from RT21HC technical grade paraffin with a nominal melting point at ~293–294 K. In order to evaluate the possible effect of paraffinic nucleating agents on those three properties, a nano–emulsion with 3.6% of RT21HC and 0.4% of RT55 (a para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 58 publications
1
7
0
Order By: Relevance
“…The total surface area among various phases of components of the nanoemulsion was thus significantly larger than the other two fuels, resulting in it being the largest kinematic viscosity among the test fuels. The result agreed well with Cabaleiro et al [29]. The nanoemulsion was also found to have the lowest carbon residue (0.26 wt.…”
Section: Resultssupporting
confidence: 91%
“…The total surface area among various phases of components of the nanoemulsion was thus significantly larger than the other two fuels, resulting in it being the largest kinematic viscosity among the test fuels. The result agreed well with Cabaleiro et al [29]. The nanoemulsion was also found to have the lowest carbon residue (0.26 wt.…”
Section: Resultssupporting
confidence: 91%
“…This Editorial note was dedicated to the 1st International Conference on Nanofluids and the 2 nd European Symposium of Nanofluids (ICNf2019). After a short report about the conference, the successful invited submissions [7][8][9][10][11][12][13][14][15] to this Special Issue of Energies were introduced. We believe that the articles in this special issue, whose main parts were presented during the conference, will contribute significantly to the development of nanofluid science and challenges in heat transfer and energy applications.…”
Section: Discussionmentioning
confidence: 99%
“…The first paper, by Cabaleiro et al [7], reports a comprehensive experimental characterization of phase change material (paraffin-in-water) nano-emulsions. The effect of dispersed phase concentrations of 2, 4 and 10 wt.% on the dynamic viscosity, surface tension and wettability of nano-emulsions is investigated, showing the impact of paraffin droplets and surfactant on these properties.…”
Section: Icnf2019: About the Selected Papers Of The Simentioning
confidence: 99%
“…They used wettability control to propose new methods to predict specific heat and thermal conductivity of molten salts and their nanofluids accurately. Moreover, Cabaleiro et al [22] found that addition of a phase change material into water decreases the CA up to 52%.…”
Section: Introductionmentioning
confidence: 99%